Dikes on permafrost: predicting thaw and settlement - Brown, W. G.; Johnston, G. H. (Canadian Geotechnical Journal, 1970)
Prediction of permafrost thaw and settlement of dikes constructed on perennially frozen ground is important for maintenance and foundation stability. A method is developed for estimating the rates of thaw and settlement, based on simple heat conduction theory. A comparison of calculated and observed rates of thaw for dikes on ice-rich foundation soils at the Kelsey Generating Station in northern Manitoba shows good agreement and indicates that thaw and settlement rates can be predicted with reasonable accuracy.